THE INFLUENCE OF FRAMING AND OBEDIENCE PRESSURE ON THE PERCEPTION OF AUDIT JUDGMENT (CASE STUDY ON ACCOUNTING STUDENT OF UNIVERSITY OF TANJUNGPURA) - YUDAS, DINA PRICILLIA B1034131012 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
ABSTRACT This research is a causal comparative study which aims to determine: (1) The Influence of Framing on the Perception of Audit Judgment, (2) The Influence of Obedience Pressure on the Perception of  Audit Judgment and (3) The Simultaneous Influence of Framing and Obedience Pressure on The Perception of Audit Judgment.The population of this research is 50 accounting students of University of Tanjungpura. It uses purposive sampling using 50 students who have taken Audit 1 and Audit Practicum courses. Data were collected using the questionnaire method. The correlation test of pearson product moment is used to validate the data and cronbach alpha is used to test its reliability. The classical assumption test includes normality test, linearity test, multicollinearity test and heteroscedasticity test. The hypothesis test of this research uses the simple linear regression analysis and the multiple linear regression analysis.The results show that: (1) There is a significant influence of Framing on the Perception of Audit Judgment which can be seen through the value of r(x1y) (0,348), the value of r2(x1y) (0,121)—the significant value is less than the level of significant (0,013 < 0,050) and the equation of the regression line Y = 45,969 - 0,850X1; (2) There is no significant influence of Obedience Pressure on the Perception of Audit Judgment which can be seen through the value of r(x2y) (0,071), the value of r2(x2y) (0,005)—the significant value is more than the level of significant (0,622 > 0,050) and the equation of the regression line Y = 25,938 + 0,135X2; and (3) There is a significant simultaneous influence of Framing and Obedience Pressure on the Perception of Audit Judgment which can be seen through the value of Ry(x1x2) (0,380), the value of R2y(x1x2) (0,144), the value of F-count (3,967) bigger than F-table (3,18) —the significant value is less than the level of significant (0,026 < 0,050) and the equation of the regression line Y = 39,650 – 0,937X1 + 0,298X2.Keywords: Framing, Obedience Pressure, and The Perception of Audit Judgment.